Optimization of the Extraction Process of Phenolic Antioxidant from Polyalthia Longifolia (Sonn.) Thawaites - Sampath M (Journal of Applied Pharmaceutical Science, 2013)
The research was carried out to optimize the extraction conditions of phenolic antioxidant from the leaves of Polyalthia longifolia. It was optimized by using L16 orthogonal design of experiment. The effect of single factors such as shaking speed, extraction time, modifier concentration and material ratio on the extraction of the phenolic antioxidant was investigated. The maximum phenolic antioxidant content was obtained under optimum conditions of shaking speed at 200 rpm, shaking time 10 min with material ratio of 1:10 and 80% of ethanol.
Keywords: Polyalthia longifolia, Orthogonal